The Everything Store: Jeff Bezos and The Age of Amazon - Brad Stone (New York Back Bay Books, 2014)
Though Amazon.com started off delivering books through the mail, its visionary founder, Jeff Bezos, was never content with being just a bookseller. He wanted Amazon to become 'the everything store', offering limitless selection and seductive convenience at disruptively low prices. To achieve that end, he developed a corporate culture of relentless ambition and secrecy that's never been cracked. Until now... Jeff Bezos stands out for his relentless pursuit of new markets, leading Amazon into risky new ventures like the Kindle and cloud computing, and transforming retail in the same way that Henry Ford revolutionized manufacturing. Amazon placed one of the first and largest bets on the Internet. Nothing would ever be the same again.
Keywords: Business; Nonfiction; Biography; Technology